Implementation of the REACT Learning Model in Mathematics Education: A Systematic Literature Review - Trian Fajrianto; Larasati Rizky Putri; Wardani Rahayu (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2025)
Mathematics education requires learning approaches that enable students to construct conceptual understanding through meaningful and contextual experiences rather than procedural memorization. One approach that aligns with this demand is the REACT learning model (Relating, Experiencing, Applying, Cooperating, Transferring). Despite its growing application, research on REACT in mathematics education, particularly in the Indonesian context, remains fragmented and tends to emphasize specific learning outcomes without systematically mapping its conceptual characteristics, implementation patterns, and reported effectiveness. Therefore, this study aims to synthesize empirical evidence on the implementation of the REACT model in mathematics learning through a Systematic Literature Review. This study employed a Systematic Literature Review (SLR) guided by the PRISMA protocol. Fifteen empirical articles published between 2015 and 2025 were selected from Google Scholar, Garuda, ERIC, and ScienceDirect databases. The selected studies were analyzed using thematic analysis and descriptive synthesis to identify trends related to REACT components, mathematics topics, educational levels, and learning outcomes. The results indicate that REACT is consistently framed as a contextual and constructivist learning approach that contributes positively to students' conceptual understanding and Higher Order Thinking Skills (HOTS). The Relating and Experiencing stages are the most frequently emphasized components, reflecting a strong focus on contextualization and active exploration. Across the reviewed studies, improvements are most commonly reported in conceptual understanding and mathematical problem-solving ability, followed by gains in mathematical communication and representation. Several studies report the use of problem-oriented tasks and technology-supported activities within the REACT framework; however, such integrations remain limited and are not examined as independent intervention models. In conclusion, the findings suggest that the REACT learning model is effective in supporting meaningful and competency-based mathematics learning. Nevertheless, the integration of REACT with other instructional models or digital media remains underexplored in the existing literature, indicating the need for future research to investigate such hybrid implementations more systematically and empirically.